Reviews. (1st March 2010) - Memou, Antigoni; Adil, Alev; Kinsman, Margaret; Paul, Richard; Smyth, Diane
You've been framed Disciplinary Frame: Photographic Truths and the Capture of Meaning, John Tagg (2009) Minneapolis, London: University of Minnesota Press, 392 pp., Hardback, ISBN 0816642877, 51.50, Paperback, ISBN 0816642885, 15.67Becoming photographic Photography, Cinema, Memory: The Crystal Image of Time, Damian Sutton (2009) Minnesota, University of Minnesota Press, 296 pp., ISBN 9780816647392, Paperback, 15.50The lure of the crime scene Lacan at the Scene, Henry Bond (2009) Cambridge, Mass.: MIT Press, 256 pp., ISBN 0262013428, Hardback, 14Re rereading Camera Lucida Photography Degree Zero, Reflections on Roland Barthes's Camera Lucida, Geoffrey Batchen (ed.) (2009) Massachusetts: MIT Press, pp. 320, ISBN 026201358, Hardback, 22.95Conference Report Humanising Photography, Durham Centre for Advanced Photography Studies (organized in partnership with Autograph ABP), 2527 September 2009